1999
DOI: 10.1152/ajpheart.1999.276.6.h2159
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-A expression correlates with blood pressure and remodeling in 1K1C hypertensive rat arteries

Abstract: Dobrian, Anca, Suzanne S. Wade, and Russell L. Prewitt. PDGF-A expression correlates with blood pressure and remodeling in 1K1C hypertensive rat arteries. Am. J. Physiol. 276 (Heart Circ. Physiol. 45): H2159-H2167, 1999.-We previously demonstrated remodeling of large and small arteries in angiotensin II-treated rats, paralleled by an increased expression of platelet-derived growth factor (PDGF)-A chain mRNA in large arteries. Both remodeling and PDGF-A expression were associated with elevation of blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…As is the case for hypertrophy itself, PDGF-A expression can be attributed to elevated pressure or stimulation of the VSMCs by hormonal factors including ANG II. Previous work from this laboratory showed that PDGF-A expression and vascular wall hypertrophy both correlate with blood pressure in the 1K1C hypertensive rat (6). Decreasing blood pressure by different antihypertensive agents in the SHR also produced a decrease in PDGF-A expression and aortic hypertrophy, both of which correlated with the change in blood pressure (29).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…As is the case for hypertrophy itself, PDGF-A expression can be attributed to elevated pressure or stimulation of the VSMCs by hormonal factors including ANG II. Previous work from this laboratory showed that PDGF-A expression and vascular wall hypertrophy both correlate with blood pressure in the 1K1C hypertensive rat (6). Decreasing blood pressure by different antihypertensive agents in the SHR also produced a decrease in PDGF-A expression and aortic hypertrophy, both of which correlated with the change in blood pressure (29).…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies in our laboratory demonstrated that PDGF-A chain but not -B chain was elevated in the aortic wall in 1K1C hypertension (6). There are significant differences between the proliferative effects of the dimeric chains on VSMCs; PDGF-BB and -AB promote DNA synthesis (25), whereas PDGF-AA is a weak mitogen (19).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lysate was purified from insoluble material by centrifugation at 14,000 g for 10 min, and protein concentrations were determined through the use of a commercially available protein assay (Bio-Rad). Equal protein levels were then loaded onto 10% SDS-polyacrylamide gels under nonreducing conditions (10). After electrophoresis, proteins were transferred to Immun-Blot polyvinylidene difluoride membranes (Bio-Rad) and were blocked with 5% milk in Tris-buffered saline containing 0.1% Tween 20 for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Thin sections of the paraffin-embedded tissue were stained for 1 min with toluidine blue and analyzed as described previously (10).…”
Section: Vascular Hypertrophy and Kidney Sclerosismentioning
confidence: 99%